2D MBenes: A Novel Member in the Flatland. Issue 23 (3rd May 2022) - Nair, Varun G.; Birowska, Magdalena; Bury, Dominika; Jakubczak, Michał; Rosenkranz, Andreas; Jastrzębska, Agnieszka M.
Abstract: 2D MBenes, early transition metal borides, are a very recent derivative of ternary or quaternary transition metal boride (MAB) phases and represent a new member in the flatland. Although holding great potential toward various applications, mainly theoretical knowledge about their potential properties is available. Theoretical calculations and preliminary experimental attempts demonstrate their rich chemistry, excellent reactivity, mechanical strength/stability, electrical conductivity, transition properties, and energy harvesting possibility. Compared to MXenes, MBenes' structure appears to be more complex due to multiple crystallographic arrangements, polymorphism, and structural transformations. This makes their synthesis and subsequent delamination into single flakes challenging. Overcoming this bottleneck will enable a rational control over MBenes' material–structure–property relationship. Innovations in MBenes' postprocessing approaches will allow for the design of new functional systems and devices with multipurpose functionalities thus opening a promising paradigm for the conscious design of high‐performance 2D materials. Abstract : 2D MBenes, early transition metal borides, have recently gained tremendous attention due to their unique properties. This Perspective sheds light on the material–structure–property relationship of MBenes and elucidates the most prospective applications in various fields, thus opening a promising paradigm for designing new functional systems and high‐performance devices with multipurpose functionalities.